SOCIAL IMPACT INVESTMENT IN GREECE: EXPLORING THE CHALLENGES AND OPPORTUNITIES FOR A MORE SUSTAINABLE SOCIETY - Karavas, Sophia A (Top Journal of Public Policy and Administration (TJPPA), 2023)
This study explores the challenges and opportunities of Social Impact Investment (SII) in Greece with a focus on promoting a more sustainable society. It examines the application of Social Impact Bonds (SIBs) by the public administration to support sustainable development and social integration, while also aiding Social Economy Organizations in fulfilling their missions of sustainable and socially inclusive development. Drawing insights from case studies in the UK, USA, and Israel, this research sheds light on the importance of Socially Responsible Public Procurement (SRPP) and the role of SIBs in fostering an inclusive and environmentally respectful society. The study delves into the theoretical underpinnings of SIBs, their relationship with public procurement, and the outcomes achieved in different contexts. By presenting the results of SIB utilization for contracting authorities, the Social Economy, and broader public policies such as employment and social inclusion, it provides valuable insights into the effectiveness of this financial instrument. In addition to its findings, this study offers proposals for improving the institutional framework of Social Impact Bonds in Greece, highlighting the advantages and disadvantages of SIBs as a means to support Social Economy Entities. By addressing the challenges and opportunities in SII, this research contributes to both theory and practice, offering valuable insights for policymakers, stakeholders, and investors interested in advancing SII in Greece.